Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 6)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 6)" [g0973006.jpg], n.d.